A Discrimination Discourse on Mongabay.Com: Indonesian Court Jails Environmentalist for Flagging Illegal Farms in Marine Park - Najwa, Nadia; Izzatunnisa , Azka (CV. Era Digital Nusantara, 2024)
This research reveals the discrimination discourse surrounding the Indonesian court's treatment of environmental activists, specifically focusing on the case of Daniel Frits, who was jailed for exposing illegal shrimp farms in Karimunjawa. The primary objective of this study is to reveal how the media, particularly Mongabay.com, represents the court's actions and the implications of this representation for environmental activism in Indonesia. Using a critical descriptive method and qualitative data, the research analyzes the language and source selection in the article titled